Implementasi Teknologi Blockchain Dalam Pengembangan Sistem E-Career Berbasis Mobile Politeknik LP3I Medan - Rahmah, Maulidya; Almadany, Khairunnisa; Khair, Rizaldy (AI Society & STMIK Indonesia, 2024)
In the current digital era, Blockchain technology has shown great potential across various sectors, including education and career development. However, its application in electronic career systems or E-Career is still rare. This creates an urgency to conduct research on how Blockchain technology can be applied in E-Career systems to enhance efficiency, transparency, and security in the career search process for students. This study aims to implement Blockchain technology in the development of an E-Career system at Politeknik LP3I Medan, based on a mobile application. One sector that can benefit from Blockchain technology is the electronic career system or E-Career. This system aims to facilitate career searches for students in a more efficient and transparent manner. However, the challenge in implementing this system lies in ensuring that data shared between different parties is secure and immutable. The main goal is to create a system that is not only efficient but also secure and transparent. Thus, students can search for careers in a more efficient and transparent way, while companies can more easily find the right candidates. Additionally, this research also aims to identify and address the challenges in integrating Blockchain technology with mobile applications.